Implementation of Digital Technology by Women Entrepreneurs in Singkawang City - Retno Larasatie; Dwi Prasetyani; Sarjiyanto Sarjiyanto (Journal of Applied Business and Technology, 2025)
Business success can increase the country's economic growth and the contribution of women in the MSME sector is 64% of the total MSMEs. Singkawang City has 39,747 women entrepreneurs who affect the welfare of the community. However, there are obstacles and limitations so that women entrepreneurs are considered not successful enough in a business. The implementation of digital technology in business is considered to be able to facilitate women entrepreneurs in facing obstacles and can provide flexibility to balance the roles and responsibilities that women have. This study aims to look at the implementation of digital by women entrepreneurs in Singkawang City with a descriptive quantitative approach by 185 respondents. This study found that the use of Whatsapp dominates the implementation of digital technology in women entrepreneurs in Singkawang City where 185 women entrepreneurs in Singkawang City use Whatsapp in their business processes. In addition, the average women entrepreneur in Singkawang City uses 3 to 4 combinations of digital technology where the most widely used combinations are Whatsapp, Facebook, Instagram and Tiktok in their business.